2016
DOI: 10.1589/jpts.28.
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balance training by knee joint motions on muscle activity in adult men with functional ankle instability

Abstract: [Purpose] This study examined the effects of balance training by applying knee joint movements on muscle activity in male adults with functional ankle instability. [Subjects and Methods] 28 adults with functional ankle instability, divided randomly into an experimental group, which performed balance training by applying knee joint movements for 20 minutes and ankle joint exercises for 10 minutes, and a control group, which performed ankle joint exercise for 30 minutes. Exercises were completed three times a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
1
11
0
3
Order By: Relevance
“…Moreover, the present study showed that the CAIT score increases were statistically significant in both the experimental and the control groups because the training improved muscle strength around the ankles and thereby reduced subjective feelings of ankle instability. The present study’s results were consistent with those of previous studies, in which balance training and muscle strengthening exercises increased muscle activity around ankles, including the tibialis anterior and peroneus longus muscles, as well as isokinetic muscular strength, improving ankle stability 1 , 14 ) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the present study showed that the CAIT score increases were statistically significant in both the experimental and the control groups because the training improved muscle strength around the ankles and thereby reduced subjective feelings of ankle instability. The present study’s results were consistent with those of previous studies, in which balance training and muscle strengthening exercises increased muscle activity around ankles, including the tibialis anterior and peroneus longus muscles, as well as isokinetic muscular strength, improving ankle stability 1 , 14 ) .…”
Section: Discussionsupporting
confidence: 92%
“…A tilt sensor detects the angle of flexion and extension of the knee joints. For example, when the knees are bent, a cursor is raised, and when the knees are extended, a cursor descends, thereby performing training to touch various fruits arranged randomly on a tree on the screen 1 , 9 ) . The visual feedback balance training was conducted three times a week for 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that balance-training program of short to moderate duration over the course of at least 4 weeks can improve objective and subjective measures of function in persons with musculoskeletal injuries (eg, CAI) and uninjured control participants. Using a progressive style, 4week balance-training programs including a combination of low-impact and dynamic activities have also improved self-assessed disability and postural control in those with CAI (1,(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with FAI were included in the study if their ages were between 20 and 30 years, had at least 1 significant unilateral inversion sprain of either ankle that resulted in pain, swelling, and loss of function within last year, followed by more than 1 repeated injury or the perception of ankle instability or "giving way", no recent lower-limb or low back pathology, no evidence of mechanical instability as assessed by the anterior drawer and talar tilt tests, no reported history of ankle injury within the last 3 months. Subjects in the FAI group had 1 to 3 ankle sprains within the previous 12 months, and the Cumberland Ankle Instability Tool (CAIT) score lower than 24 [24][25][26][27].…”
Section: Study Subjectsmentioning
confidence: 99%